Redescription and sexual dimorphism of Andaman leg‐skate Cruriraja andamanica (Chondrichthyes: Rajiformes) with comments on the zoogeography of the genus Cruriraja. Issue 2 (August 2017) - Vinu, J.; Rajeeshkumar, M. P.; Parmeswaran, U. V.; Sumod, K. S.; Akhilesh, K. V.; Manjebrayakath, H.; Sanjeevan, V. N.
Abstract : This paper redescribes sexually dimorphic Cruriraja andamanica based on five juvenile (four males, one female) and four adult specimens (three males, one female) collected from Andaman waters. Morphometric comparison of the present specimens with a female specimen collected off the coast of Tanzania reveals considerable dissimilarities between them. These findings, along with the wide geographical distance between collection locations, support a need for revision of the Tanzanian specimen, which, in all probability, represents a new species in the genus. The paper also addresses zoogeography of genus Cruriraja across the world's oceans and provides a revised key to the species.